PERANCANGAN DAN PEMBUATAN MESIN PENGAMPELAS PERMUKAAN MENGGUNAKAN AMPELAS PITA YANG DIGERAKKAN MOTOR LISTRIK - Nurlatif, Fahrul; Nuhgraha, Yoddy Agung (Jurnal Mahasiswa Terapan; Vol 1 No 1 (2024): Jurnal Mahasiswa Terapan, 2024)
Sanding is a process of working on a workpiece to obtain a smooth and even surface, by rubbing the sandpaper blade on the workpiece, so that the surface of the workpiece will be eroded. Students generally use stone grinders. The use of grinding stones in mechanical workshops has disadvantages such as convex grinding surface results. This problem can be overcome by making a belt grinder. Sanding belt as a tool in the grinding process. The activity of making this belt grinder machine aims to remove and smooth the sharp edges on the metal surface. In addition, this activity aims to help students at the TEDC Bandung Polytechnic in carrying out the teaching and learning process in mechanical workshops. In this regard, the activity of making a belt grinder machine consists of 4 stages, namely: the design stage, manufacture, assembly and testing stage of the belt grinder machine. Based on the results of the test and discussion, it can be concluded that the use of a sanding belt as a grinding tool can eliminate sharp edges on metal. The design shape of the sanding machine adjusts to the shape of the motor and the length of the sandpaper itself so as to find an ideal and more appropriate design.